THE ROLE OF ADVANCED TECHNOLOGY IN TEACHING BIOLOGY - Gulomova Guli Abdusamatovna, Makhmadiyorova Motabar Toshkanovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the modern educational environment, information technologies play a crucial role in enhancing teaching and learning processes. In biology education, integrating advanced technologies has become a necessity to make complex concepts more accessible and engaging. This article discusses the significance of information technologies in teaching biology, focusing on their ability to facilitate interactive learning, improve accessibility, and increase educational efficiency. By utilizing tools such as virtual laboratories, simulation software, and digital platforms, educators can provide students with innovative approaches to learning biological concepts. The abstract also highlights the challenges of implementing these technologies and emphasizes the need for further investment in training educators and upgrading educational infrastructure to maximize the benefits of digital tools in biology education.